GENETIC VARIABILITY STUDIES OF BENNISEED (Sesamum indicum Linnaeus) ACCESSIONS IN NIGER - Amaefula, G. I.; Gana, A.S.; Tolorunse, K.D.; Omonomo, P.; Adeyemo, B.D.; Unanaonwi, J.E. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study evaluated genetic variability among sixteen (16) benniseed accessions in Nigeria with the aim of identifying superior genotypes for yield and shattering resistance. Field trials were conducted at Badeggi and Mokwa using a randomized complete block design (RCBD) with three (3) replications. Data were collected on agronomic, phenological, yield, and shattering traits. The results revealed a significant (P ≤ 0.05) genetic variability among the accessions for all traits studied, indicating good potential for selection and improvement. Genotype NGB02756 consistently exhibited superior performance in terms of yield (826.61g) across both locations, while NGB04125 (2) and NGB03209 shows high resistance to shattering (0.52% and 0.57% respectively). High heritability estimates were observed for key yield-related traits which ranges from 17% to 96%, Principal component analysis which extracted the first five (5) components explaining 84% of total variation further revealed that a few major traits contributed most to the total variation among the genotypes. Cluster analysis grouped accessions into three distinct clusters, with Cluster II containing the high-yielding genotypes. NGB02756 is recommended for variety release, while NGB04125 (2) and NGB03209 are valuable sources of shattering resistance. The study highlights the potential of these genotypes for use in breeding programmes aimed at improving yield and reducing harvest losses in benniseed production in Nigeria.